2011
DOI: 10.1007/s10585-011-9383-y
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of galectin-3 in the host attenuates metastasis of murine melanoma by modulating tumor adhesion and NK cell activity

Abstract: Galectin-3, a β galactoside-binding lectin, plays an important role in the processes relevant to tumorigenesis such as malignant cell transformation, invasion and metastasis. We have investigated whether deletion of Galectin-3 in the host affects the metastasis of B16F1 malignant melanoma. Galectin-3-deficient (Gal-3(-/-)) mice are more resistant to metastatic malignant melanoma as evaluated by number and size of metastatic colonies in the lung. In vitro assays showed lower number of attached malignant cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 68 publications
2
54
0
3
Order By: Relevance
“…Specifically, galectin-3 reduces glioma cell migration (121). In general, however, galectin-3 (107) is mostly associated with increased invasive behavior in most cancer cell types tested (94,95,117,(122)(123)(124)(125)(126), supporting the view that targeting this galectin might be a promising avenue for the treatment of many types of cancer. Whether this is also true for other galectins has to be determined.…”
Section: Galectin (%) Cellular --------------------------------------mentioning
confidence: 95%
“…Specifically, galectin-3 reduces glioma cell migration (121). In general, however, galectin-3 (107) is mostly associated with increased invasive behavior in most cancer cell types tested (94,95,117,(122)(123)(124)(125)(126), supporting the view that targeting this galectin might be a promising avenue for the treatment of many types of cancer. Whether this is also true for other galectins has to be determined.…”
Section: Galectin (%) Cellular --------------------------------------mentioning
confidence: 95%
“…+ T cells in wild type mice, but not in Galectin-3-deficient mice (86). Thus, our findings suggest that hostderived Galectin-3 could lead to an increase in the number and percentage of Treg cells, which promotes the formation of an immunosuppressive tumour network and can be one of the main facilitative mechanisms important for tumour metastasis.…”
Section: Foxp3mentioning
confidence: 64%
“…In an experimental model of B16-F1 murine melanoma, we demonstrated that Galectin-3-deficient mice were more resistant to metastatic melanoma, as evidenced by markedly reduced number and size of lung metastatic colonies compared with wild type mice. In addition, by in vitro assay we noticed lower numbers of attached malignant cells in lung tissue sections of Galectin-3-deficient mice, suggesting that hostderived Galectin-3 plays a pivotal role in tumour cell adhesion to the metastatic target (86). Recently, it has been shown that Galectin-3, which is expressed in lungs (especially on the vascular endothelium), cooperates with poly-N-acetyl-lactosamine on N-glycans on B16-F1 murine melanoma cells, as a ligand for Galectin-3 (87).…”
Section: Protumourigenic Role Of Galectin3mentioning
confidence: 84%
See 2 more Smart Citations